Prevalence and incidence of multiple sclerosis in Bulgaria - Nikolova, Antonia; Milanov, Ivan; Kmetska, Ksenia (Frontiers in Neurology, 2025)
BackgroundMultiple sclerosis (MS) is a chronic, inflammatory, autoimmune, demyelinating and neurodegenerative disease of the central nervous system that primarily affects young, active people and is a leading cause of non-traumatic, irreversible neurological deficit. Multiple sclerosis is one of the most studied diseases in neuroepidemiology and is characterized by an uneven geographical distribution worldwide.ObjectiveTo estimate the prevalence and incidence of multiple sclerosis in Bulgaria and their distribution by age and gender, using data from the latest population census in the country, provided by the National Statistical Institute.MethodsAn epidemiological study, covering a 7-year period—from 2015 to 2021 was conducted in Bulgaria. Eight regions with their population were included in the study—Blagoevgrad, Montana, Pernik, Svoge, Smolyan, Troyan, Haskovo and Shumen. Data, provided by the National Statistical Institute, were used to calculate the values of prevalence and incidence of multiple sclerosis. All cases were diagnosed using the 2017 McDonald’s diagnostic criteria. The results obtained from the study were also used to determine the clinical characteristics of the Bulgarian patient. For the purposes of the epidemiological study an individual questionnaire was developed.ResultsOn the prevalence day—07.09.2021, there were 532 people with multiple sclerosis in the studied regions of the country, revealing a prevalence of 121.2/100000 and an incidence of 4.2/100000. 182 of them were males and 350 were females comprising a ratio of 2:1 in favor of the women. More than 50% of all cases had relapsing–remitting course of disease. Secondary-progressive MS had 30% of all patients and 10% suffered from primary progressive multiple sclerosis. Clinically isolated syndrome was present in less than 5% of patients. The mean age at disease onset was 32.2 ± 10.3 years.ConclusionThe established values of prevalence and incidence position Bulgaria in the area with a high frequency of MS. There is an increase in prevalence and incidence compared to previous studies conducted in the country. The results obtained are similar to those reported by the neighboring countries of the Balkan Peninsula and are close to the average values in Europe according to the latest edition of Atlas of Multiple Sclerosis.